2007
DOI: 10.1099/ijs.0.65190-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships within the family Halobacteriaceae inferred from rpoB′ gene and protein sequences

Abstract: In order to clarify the current phylogeny of the haloarchaea, particularly the closely related genera that have been difficult to sort out using 16S rRNA gene sequences, the DNA-dependent RNA polymerase subunit B9 gene (rpoB9) was used as a complementary molecular marker. Partial sequences of the gene were determined from 16 strains of the family Halobacteriaceae. Comparisons of phylogenetic trees inferred from the gene and protein sequences as well as from corresponding 16S rRNA gene sequences suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…and RpoB 0 trees (Figure 4) (Walsh et al, 2004;Enache et al, 2007;Minegishi et al, 2010). Collectively, these patterns suggest that trehalose production is an ancient trait within the Halobacteriales rather than a recent acquisition through horizontal gene transfer.…”
Section: Transcriptional Analysis Of Trehalose Synthesis Genes In H mentioning
confidence: 92%
See 1 more Smart Citation
“…and RpoB 0 trees (Figure 4) (Walsh et al, 2004;Enache et al, 2007;Minegishi et al, 2010). Collectively, these patterns suggest that trehalose production is an ancient trait within the Halobacteriales rather than a recent acquisition through horizontal gene transfer.…”
Section: Transcriptional Analysis Of Trehalose Synthesis Genes In H mentioning
confidence: 92%
“…several gene loss events during Halobacteriales evolution. otsAB genes were present in all members of Halobacteriales Clade I (as defined by Walsh et al (2004), Enache et al (2007) and Minegishi et al (2010), including the genera Halovivax, Natronobacterium, Halobiforma, Natronorubrum, Haloterrigena, Halopiger, Natronolimnobius, Natrinema, Natrialba and Natronococcus), as well as the genera Halococcus, Haladaptatus, Halalkalicoccus and Halosimplex. On the other hand, otsAB genes were absent in all members of Halobacteriales clade II (as defined by Walsh et al (2004), Enache et al (2007), Minegishi et al (2010), including the genera Haloferax, Halorubrum, Halogeometricum, Haloquadratum, Haloplanus and Halobaculum), the Halorhabdus-Halomicrobium-Haloarcula clade, as well as within the genera Halobacterium and Natronomonas.…”
Section: Transcriptional Analysis Of Trehalose Synthesis Genes In H mentioning
confidence: 99%
“…A number of haloalkaliphilic species have been discovered in soda lakes in Egypt, Kenya, China, India, and the western United States [101]. All archaeal alkaliphiles are halophiles [102, 103].…”
Section: Haloalkaliphilic Proteinsmentioning
confidence: 99%
“…Recently, DNA-dependent RNA polymerase subunit B' gene and protein sequences have been used as an alternative molecular marker in phylogenetic analysis of the family Halobacteriaceae [9,10]. Our unpublished data of the sequences of RNA polymerase H, B" and B' genes of all species of the family Halobacteriaceae (manuscript in preparation) also suggested that the strain MH1-52-1 was a representative of a novel genus.…”
Section: Resultsmentioning
confidence: 91%